Studi Komparasi Pengaruh Kecepatan Potong Tinggi dan Konvensional terhadap Kekasaran Permukaan dan Waktu Proses Bubut - Joachim, Daniel; Rosehan , Rosehan; Lubis , Sobron Yamin (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The number of manufacturing industry growth in Indonesia is increasing over time. Based on the data obtained, the manufacturing industry in Indonesia recorded growth of 3.9% from July to August 2020. This study aims to analyze the effect of cutting speed on the surface roughness of S45C steel and to find out the production time for high speed cutting machining processes. This study used an experimental method, using a transverse/cylindrical turning method. Transverse turning is a lathe process when the cutting tool moves parallel or linear to the spindle axis. The test specimen will be machining starting with determining the independent parameters; feed (f) 0.2mm/rev, depth of cut (depth of cut) 0.1mm, length of cut (Lt) 100mm, then determine the dependent parameter by varying the speed of cut (Vc) starting from 125m/min to 625m/min. Based on the results of the test data obtained, it shows that (1) The higher the cutting speed, the lower the surface roughness value. This is caused by the process of plastic deformation and thixotropy phenomena. (2) The higher the cutting speed, the lower the cutting time. This is caused by the annealing phenomenon during the turning process.